Effects of jet nebulization on ventilator performance with different invasive ventilation modes: A bench study - Li, Xinyu; Tan, Wei; Zhao, Hongwen; Wang, Wei; Dai, Bing; Hou, Haijia (Frontiers in Medicine, 2022)
Background The effects of jet nebulization on ventilator performance in the volume control mode (VC) and pressure control mode (PC) of ventilation have not been determined. Objectives The present study investigated the impact of jet nebulization on ventilator performance in different modes in vitro. Methods Two types of jet nebulizer (ventilator-integrated jet nebulizers, external jet nebulizer) and six types of ventilator were connected with a simulated lung to simulate aerosol therapy during mechanical ventilation. The ventilation modes were set to VC and PC, and the driving flows of external jet nebulizer were set at 4 L/min and 8 L/min, respectively. Jet nebulizers were placed between patient airway and Y-piece or at 15 cm from the Y-piece in the inspiratory limb. The effects of jet nebulization were compared with the baseline of triggering performance, control performance, and tidal volume under different experimental conditions. Results Ventilator-integrated jet nebulizers had no effect on ventilator performance in different modes (all P > 0.05). However, the effects of external jet nebulizers on ventilator performance varied widely: for triggering performance, all parameters were increased in different modes and nebulization positions (all P < 0.05), including the time from the beginning of the inspiratory effort to the lowest value of airway pressure needed to trigger the ventilator (TPmin), the time to trigger (Ttrig), and the magnitude of airway pressure drop needed to trigger (Ptrig); for control performance, peak inspiratory pressure (Ppeak) and peak inspiratory flow(Pflow) were increased in the VC mode (P < 0.05), but not significantly changed in the PC mode (P > 0.05);the actual tidal volume (VT) and expiratory tidal volume monitored (VTe) were significantly increased (P < 0.05), however, the inspiratory tidal volume monitored (VTi) was not affected by jet nebulization in the VC mode. In the PC mode, there were no significant changes in VT, whereas VTi decreased and VTe increased (P < 0.05). The higher the driving flow of external jet nebulizers, the stronger the impact on ventilator performance (all P < 0.05). Conclusion Triggering performance was decreased in both the VC and PC modes when using an external jet nebulizer, while the effects of nebulization on control performance and tidal volume varied significantly.